V VARIASI STRUKTUR FRASE DALAM CERPEN DAGANG CANANG - Adi Upadana, I Wayan; Dedy Herawan, Kadek (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2023)
Linguistics is a science that studies languages. Balinese language is the language used by Balinese people to communicate. Language is also used in expressing the sense of human art, for example making a literature work. In this study examines the use of grammar in a literature work, the object of research is a phrase. A phrase is a construction built by constituents with various categories or classes of words. There are many variations that will form in a phrase. As a research subject using a short story entitled Dagang Canang. Based on data analysis of variations in Balinese phrase structure in Dagang Canang short stories, among others: (1) Variations in Balinese Nominal Phrase Structure in Dagang Canang Short Stories as follows: noun phrases with Noun + Noun pattern (N + N), Noun + Adjective (N + Adj), Adverbs + Noun (Adv + N). (2) Variations of Balinese Verbal Phrase Structure in Dagang Canang Short Story as follows: Verbal Phrase with Verbal + Verbal pattern (V + V), Verbal + Adjective (V + Adj), Adjective + Verbal (Adj + V)